Analysis of The Relationship of Information Media and Knowledge With Formula Feeding In Babies Aged 6-24 Months - Efgivia, M. Givi; Sumarmi, Hj.; Khaerudin, M. (Akademi Keperawatan RSPAD Gatot Soebroto, 2021)
Mothers certainly know that the main intake for babies is breast milk. However, in some cases, babies are forced to be fed infant formula to replace breast milk if according to medical indications and on the advice of medical personnel. Always consult a medical professional for the use of infant formula. Although the content is different from breast milk, now infant formula has been formulated with various kinds of nutrients that are good for baby's growth and development. For this reason, so that babies get adequate nutrition for their growth and development, the dose of baby's milk must be adjusted to their age and weight. The purpose of this study was to determine the factors associated with formula feeding in infants aged 0-6 months. The research method used in this study is a cross sectional survey method. The population in this study were all mothers who had babies 0-6 months totaling 34 people. Samples were taken by total sampling, that is, the entire population was sampled. The results of this study prove that there is a relationship between information media, education, work and knowledge with the provision of formula milk to infants aged 0-6 months at the Rengas Health Center in 2019.